Molecular epidemiological investigation of abnormal hemoglobin in Shaokwan region, southern China. Issue 1 (31st December 2022) - Yang, Hui; Lin, Min; Lin, Fen; Ma, Zhan-Zhong; Zhan, Xiao-Fen; Yang, Li-Ye
ABSTRACT: Objectives: Shaokwan is one of the inhabitant regions of Hakka population in Guangdong province of southern China. Previous survey has reported that a higher prevalence of abnormal hemoglobin (Hb) in this region. However, large-scale survey on the molecular characteristics of abnormal hemoglobin in this south-north junctional region has not been reported.In this study, we aim to investigate the molecular characteristics of abnormal hemoglobin in this area. Methods: Blood samples from medical check-up center in one local hospital were selected for abnormal hemoglobin screening. Hemoglobin electrophoresis and routine blood tests were performed. Hemoglobin variants were further analyzed by PCR and DNA sequencing. Results: Among the 9731 study subjects, 45 cases of hemoglobin variants were found by hemoglobin electrophoresis, which gave an incidence of 0.46% (45/9731) in Shaokwan region. 8 kinds of hemoglobin variants were identified by gene sequencing. Hb Q-Thailand (16/45) was the most common hemoglobin variants, followed by HbE (7/45), Hb NewYork (6/45) and Hb G-Chinese (6/45). Discussion and Conclusion: Hemoglobin variants had obviously genetic polymorphisms in Chinese. Our study of hemoglobin disorders in this special Hakka Chinese population will contribute considerably to our understanding of the historical, emigrational, and genetic relationships among different ethnic group in this region.